Fabrication of magnetic activated carbon from spent coffee ground by hydrothermal synthesis for methylene blue removal. Issue 1 (February 2021) - Rizkiana, M F; Hidayatullah,; Rosalina, A; Fachri, B A; Harada, H
Abstract: Spent coffee ground-based magnetic activated carbon (MSC) was prepared using hydrothermal synthesis and utilized for the adsorption of methylene blue (MB). The MSC was made using the following conditions: the molar ratio of ferrous/ferric ions was 1:1.5, the hydrothermal treatment at 126°C for 2 h. The prepared MSC was investigated for surface morphology and chemical structure using FTIR and SEM. Batch adsorption studies were performed at 308 K; 318 K and MB concentration of 50-400 mg L −1 to evaluate the adsorption behaviour. The results showed as follows: there were C=O, C=C, C-O, Fe-O groups on the MSC surface and magnetite existed in the pores and surfaces of the MSC. Sorption behaviour at different temperatures were evaluated using the Langmuir, Freundlich, Temkin models, confirming Freundlich model was fitted on MSC. First and second order kinetic models were tested and the data fitted the first order behaviour. The adsorption process was a spontaneous, endothermic, and more reactive upon raising the temperature. After adsorption, MSC could be separated by applying magnetic field. Magnetic removal would allow convenient tool for adsorbent separation from contaminated water.